A REVIEW OF MARINE NATURAL PRODUCTS AS POTENTIAL SOURCE OF ANTIOXIDANTS - Rhesa Hinampas; Angelo Mark Walag (SEAMEO BIOTROP, 2024)
Article Highlights- Marine Natural Products have been the most favorable source of bioactive compounds for drug discovery research.- Many biologically active chemicals with antioxidant properties can be found in the marine environment.- A systematic review on potential source of antioxidants linked to marine natural products was carried out.- Algae, fungi, sponges, mollusks, and sea cucumbers were found to be abundant sources of antioxidants.- Integrate these discoveries into practical applications for enhancing human health and well-being. AbstractSeveral diseases have been linked to oxidative stress, resulting from an imbalance between the creation of the body’s antioxidant defense mechanisms and reactive oxygen species (ROS). Due to their distinct metabolic makeup and wide range of biological adaptations, marine organisms have attracted interest as possible sources of new antioxidants. This systematic review aims to evaluate the antioxidant potential of marine natural products. To find relevant research published between 2002 and 2022, a thorough search strategy based on the PRISMA standards was used across databases, including PubMed, Google Scholar, Mendeley, and Science Direct. A total of 18 studies were extracted and included in the review. The results consistently showed that marine natural compounds had vigorous antioxidant activity. Algae, fungi, sponges, mollusks, and sea cucumbers were shown to be abundant sources of antioxidants in marine environments. Flavonoids, alkaloids, phenols, tannins, steroids, saponins, glycosides, terpenoids, and carotenoids are only a few types of marine natural products that have been discovered to possess strong antioxidant properties. This systematic review provides compelling evidence for the antioxidant potential of marine natural products. The research validates their potential as sources of novel antioxidants with various bioactive properties. Unlocking the full potential of marine natural products and integrating these discoveries into practical applications for enhancing human health and well-being calls for further research.